The influence of service quality from PT Kereta Api Indonesia (Persero) on customer satisfaction at PT Bukit Asam Tbk - Saputra, Mohammad Reza; Widiyanti, Marlina; Shihab, Muchsin Saggaf; Maulana, Ahmad (International research journal of management, IT and social sciences, 2024)
This study examines the effect of service quality provided by PT Kereta Api Indonesia (Persero) on the level of corporate customer satisfaction, specifically PT Bukit Asam Tbk. As a user of railway transportation services for coal logistics, PT Bukit Asam requires quality services to ensure smooth and efficient operations. This research uses quantitative methods with a sample of 100 respondents consisting of PT Bukit Asam Tbk employees involved in the logistics process. Data obtained through questionnaires were analyzed using multiple linear regression. The results showed that the service quality of PT Kereta Api Indonesia has a positive and significant influence on PT Bukit Asam’s customer satisfaction, with the indicator of friendly service and responsiveness of the officers scoring the highest. These findings suggest that improving service quality can strengthen customer satisfaction and loyalty.